2015
DOI: 10.1309/lmjqnoqcfg4gkqrj
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Transfusion Ratios in Massive Transfusion Protocols: An Argument Against the 1:1:1 Dogma and Approach to Trauma Resuscitation

Abstract: We believe that the current practice of transfusing red blood cells (RBCs), plasma, and platelets in a 1:1:1 ratio is not optimal in massive transfusion protocols (MTPs) and is based on a simple yet profound misconception regarding the preparation of component blood products. This 1:1:1 approach ignores the additional fluids added for anticoagulation and preservation of the components and assumes that there is a one-size-fits-all ratio that must be used across all types of trauma. In this article, we explain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Concordant with the related literature, whole blood reconstituted at a 1:1:1 ratio had only limited oxygen‐carrying capacity (median hematocrit, 30% in both FFP200 and LP200) and reduced coagulation proteins (compared with the pure FFP or LP units) because of the mutual dilution of RBCs, plasma, and platelets. The use of low‐volume LPs allowed us to reduce the extent of dilution on the cellular count (higher hematocrit and platelet count) and coagulation factors (increased fibrinogen and both procoagulant and anticoagulant levels) compared with the other two groups.…”
Section: Discussionsupporting
confidence: 85%
“…Concordant with the related literature, whole blood reconstituted at a 1:1:1 ratio had only limited oxygen‐carrying capacity (median hematocrit, 30% in both FFP200 and LP200) and reduced coagulation proteins (compared with the pure FFP or LP units) because of the mutual dilution of RBCs, plasma, and platelets. The use of low‐volume LPs allowed us to reduce the extent of dilution on the cellular count (higher hematocrit and platelet count) and coagulation factors (increased fibrinogen and both procoagulant and anticoagulant levels) compared with the other two groups.…”
Section: Discussionsupporting
confidence: 85%
“… 3 , 5 , 35 38 When taking this into account, the ratio 1:1:1:1, which includes fibrinogen, seems to be very smart and advantageous. 3 , 5 , 14 , 21 , 25 , 36 38 …”
Section: Component Therapymentioning
confidence: 99%
“… 5 , 3 , 35 38 Therefore a single injection of fibrinogen concentrate at a dose of 2–4 g intravenously seems to be a smart and useful intervention. 3 , 5 , 14 , 21 , 25 , 36 38 There is no evidence that cryoprecipitate would improve the outcome of patients with low fibrinogen levels caused by massive bleeding. 43 Hypothermic coagulopathy is very challenging to treat in bleeding patients, but it was shown that coagulopathy caused by hypothermia can be reversed and successfully corrected by fibrinogen concentrate.…”
Section: Fibrinogenmentioning
confidence: 99%
“…From a theoretical standpoint, a 2:1 ratio of PRBC to FFP by volume has been proposed in order to maintain adequate coagulation factor activity as well as oxygen carrying capacity. 21 The theoretical risk of improperly proportioned ratios (by volume) in children is magnified as the total circulating blood volume decreases. Moreover, an analysis of the Department of Defense Trauma Registry demonstrated that a low ratio of PRBC to FFP (approaching 1:1 by volume) increased the odds of mortality of pediatric patients receiving any blood product within the first 24 hours of trauma admission.…”
Section: Discussionmentioning
confidence: 99%